Know your open source code. Issue 5 (May 2016) - Pittenger, Mike
Abstract : Open source software use has moved from the fringes into the mainstream of software development, accelerating time to market and generating cost savings. But despite these benefits, a thoughtful approach to adoption is essential. Lack of visibility into the open source software in use – particularly to known open source security vulnerabilities that have found their way into the codebase – exposes organisations to exploitation that could result in financial losses, business disruption, customer defection, legal action and brand risk. Open source software use has moved from the fringes into the mainstream of software development, accelerating time to market and generating cost savings. However, a thoughtful approach to adoption is essential, says Mike Pittenger of Black Duck Software. Lack of visibility into the open source in use – particularly to known security vulnerabilities that have found their way into the codebase – exposes organisations to exploitation that could result in financial losses, business disruption, customer defection, legal action and brand risk.